Hierarchical Porous Carbon-PtPd Catalysts and Their Activity toward Oxygen Reduction Reaction - Arias Pinedo, Ofelia M. (2022)
PtPd bimetallic catalysts supported on hierarchical porous carbon (HPC) with different porous sizes were developed for the oxygen reduction reaction (ORR) toward fuel cell applications. The HPC pore size was controlled by using SiO2 nanoparticles as a template with different sizes, 287, 371, and 425 nm, to obtain three HPC materials denoted as HPC-1, HPC-2, and HPC-3, respectively. PtPd/HPC catalysts were characterized by scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, and high-resolution transmission electron microscopy. The electrochemical performance was examined by cyclic voltammetry and linear sweep voltammetry. PtPd/HPC-2 turned out to be the most optimal catalyst with an electroactive surface area (ESA) of 40.2 m2 g?1 and a current density for ORR of −1285 A g?1 at 2 mV s?1 and 1600 rpm. In addition, we conducted a density functional theory computational study to examine the interactions between a PtPd cluster and a graphitic domain of HPC, as well as the interaction between the catalyst and the oxygen molecule. These results reveal the strong influence of the porous size (in HPC) and ESA values (in PtPd nanoparticles) in the mass transport process which rules the electrochemical performance.